Keutamaan dan Adab Membaca Al-Qur’an dalam Pembentukan Karakter Muslim - Muhajir; Robiatul Adawiah; Bayu Endru Subiyakto; Irfan Fauzan (PT. Hasba Edukasi Mandiri, 2026)
The Qur’an is the primary source of Islamic teachings and serves as a guide for life and a foundation for the formation of human character. Reading the Qur’an is not only an act of worship but also a means of moral development, spiritual education, and personal growth based on divine values. However, recitation that attains true excellence must be accompanied by the proper etiquette as explained by Islamic scholars. This study aims to analyze the virtues and etiquette of reading the Qur’an and the role of both in shaping Muslim character. The method employed is a literature review by examining 15 scholarly sources in the form of journals and undergraduate theses. The results indicate that the virtues of reading the Qur’an lie not merely in the act of recitation, but also in reflection, practice, and the observance of proper etiquette. Reading the Qur’an with proper etiquette is able to shape Muslim character that is knowledgeable, morally upright, and responsible toward Qur’anic values.